Changes in Kerogen and Mineral Matrix Characteristics of Rocks of Bazhenov Deposits during Laboratory Modelling of Hydrothermal Processes - G. G. Savostin; A. G. Kalmykov; A. P. Vaitekhovich; N. V. Pronina; D. A. Griaznova; D. A. Marunova; G. A. Kalmykov (Georesursy, 2024)
The paper presents the results of the study of rock samples from Bazhenov deposits before and after laboratory modelling of hydrothermal processes in autoclaves. To evaluate the influence of hydrothermal influence on rocks of different degrees of transformation, 3 samples from the well, the rocks in which are located at the very beginning of the main zone of oil formation (PK3–MK1), and 4 samples from the well, the rocks in which are located in the middle of generation (MK2–MK3) were studied. Comparison of samples before and after heating was carried out by means of pyrolytic, coal petrography studies and analyses of polished section under scanning electron microscope. It is shown that at 350 °C there is a change in pyrolytic characteristics of the rock, which depends on the nature of organic matter and the degree of catagenetic transformation of kerogen at the time of exposure. It was found that as a result of exposure the initial macerals decrease in size and change their luminescence in ultraviolet light, secondary (kerogenic) porosity appears in onychite fragments. New minerals, in particular barium zeolites, are formed in the rocks. Identification of such formations in natural objects may indicate the occurrence of local temperature processes, which may lead to heterogeneity of organic matter transformation in Bazhenov sediments and should be taken into account to identify local zones of increased catagenesis.